2009
DOI: 10.1152/ajplung.90462.2008
|View full text |Cite
|
Sign up to set email alerts
|

MMP dependence of fibroblast contraction and collagen production induced by human mast cell activation in a three-dimensional collagen lattice

Abstract: Mast cell-fibroblast interactions may contribute to fibrosis in asthma and other disease states. Fibroblast contraction is known to be stimulated by coculture with the human mast cell line, HMC-1, or by mast cell-derived agents. Matrix metalloproteinases (MMPs) can also mediate contraction, but the MMP-dependence of mast cell-induced fibroblast contractility is not established, and the consequences of mast cell activation within the coculture system have not been fully explored. We demonstrate that activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 60 publications
6
22
0
Order By: Relevance
“…To generate human primary mast cells, CD34-positive progenitors were purified from PBMC, as previously described [41]. Cells were cultured in Iscove's medium containing glutamine (Lonza, Walkersville, MD, USA), 100 ng/ml SCF (R&D Systems, Minneapolis, MN, USA), 3% 209 concentrated conditioned medium generated from HCC2157 BL lymphoblastoid cell line (ATCC), and 10 pg/ml GM-CSF (R&D Systems) at 10 4 cells/ml.…”
Section: Primary Mast Cell Activationmentioning
confidence: 99%
“…To generate human primary mast cells, CD34-positive progenitors were purified from PBMC, as previously described [41]. Cells were cultured in Iscove's medium containing glutamine (Lonza, Walkersville, MD, USA), 100 ng/ml SCF (R&D Systems, Minneapolis, MN, USA), 3% 209 concentrated conditioned medium generated from HCC2157 BL lymphoblastoid cell line (ATCC), and 10 pg/ml GM-CSF (R&D Systems) at 10 4 cells/ml.…”
Section: Primary Mast Cell Activationmentioning
confidence: 99%
“…We have recently used a contraction model with collagen gels coembedded with human lung fibroblasts and mast cells to study cellular interactions contributing to fibrosis (18). We now adapt this system to model mast cell interactions with human airway smooth muscle cells (HASM) and explore the consequences of human mast cell activation in coculture with smooth muscle cells in the collagen gel matrix.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25] In this study, the MMP production and activity was measured in cells cultured in 3D collagen gels under static conditions, therefore no extrinsic load was applied to the gels. Gels remained tethered throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that general MMP inhibitors can prevent fibroblast-induced gel contraction. 20,24,28,29 Although specific MMPs involved have not been identified, MMP-2 and -9 have been implicated. 30,31 Other studies have suggested that fibroblasts exhibit contractile force independent of MMPs 32 through alteration in the cytoskeleton and cell-cell interactions.…”
Section: Discussionmentioning
confidence: 99%